Effectiveness of stewardship and management strategies to conserve coastal bird populations in the northern Gulf of Mexico: a literature review - Jennifer L Fuller; Nicole L Michel; Evan M Adams; Abigail J Darrah; Auriel M. V. Fournier; Jacquelyn K Grace; Lianne Koczur; Bethany A. C. Kraft; Terri J Maness; Sarah P Saunders; Caz M Taylor; Kiara L Valentine; et al. (Journal of Field Ornithology)
Shorebirds, seabirds, and wading birds (hereafter coastal birds) have experienced considerable losses over the last century and require proactive conservation management to stabilize or grow populations. Habitat loss and/or degradation and human disturbance are among the most urgent threats faced by coastal bird populations. Identifying effective conservation management techniques to mitigate these threats is of great interest in the northern Gulf of Mexico (nGoM), a region that provides important habitat during the entire life cycle of resident birds and an essential breeding, wintering, and stopover site for migratory birds. A suite of 35 coastal birds have been identified as priority species for multi-scale conservation monitoring in this region by the Gulf of Mexico Avian Monitoring Network (GoMAMN). This review focuses on impacts of human disturbance and anthropogenic habitat loss and/or degradation on coastal birds and effectiveness of the management strategies implemented to mitigate them, with the goal of informing nGoM management. Our review found that human disturbance was best alleviated by simultaneously deploying complementary stewardship techniques (e.g., signs, fencing, steward patrols, education and community involvement, and beach closures to humans, dogs, and vehicles). However, the relative efficacy of each individual technique is unclear given that only 13% of human disturbance management studies and 38% of habitat management studies have been conducted in the nGoM region. Given the nature of coastal bird habitat and associated risks from sea level rise and human development, most habitat management studies encouraged strategic applications of beach renourishment, limitations on beach raking, as well as site- and species-specific restoration strategies. Studies demonstrated that successful management of coastal birds in the nGoM combined these approaches, employing complementary and adaptive strategies over extended periods.